The Commodification of Da'wah on Social Media: A Critical Discourse Analysis of Monetized Da'wah Content on YouTube - M. Syarif Thoyib (Almustofa Journal of Islamic Studies and Research, 2026)
Digital transformation has brought significant changes to “dakwah” (Islamic outreach) practices, shifting from conventional communication spaces to platform-based digital environments such as YouTube. This development has not only expanded the reach of Islamic messages but has also transformed the processes of producing, distributing, and consuming “dakwah” content. As an algorithm- and monetization-driven medium, YouTube has given rise to a new phenomenon in which religious messages, preachers, and audience attention are commodified within the digital economy. This study aims to analyze the forms of “dakwah” commodification in monetized YouTube content, the discursive strategies employed in constructing digital “dakwah”, and the interplay between religious values, the digital economy, and popular culture.The study employs a qualitative approach utilizing Norman Fairclough’s Critical Discourse Analysis (CDA) framework, which examines discourse across three dimensions: text (text level), discursive practice, and social practice. Data were gathered through digital observation, documentation of YouTube “dakwah” content, analysis of monetization elements, and observation of audience interactions. The analysis draws upon Mosco’s theory of media commodification, encompassing the commodification of content, audiences, and media labor.The findings reveal that digital “dakwah” undergoes three primary forms of commodification. First, content commodification occurs through the packaging of religious messages using popular strategies such as persuasive titles, emotional narratives, and algorithmic optimization. Second, the commodification of preachers (“dai”) occurs through personal branding practices that turn them into media figures with economic value. Third, audience commodification occurs as user attention, interaction, and data become sources of value within the platform's monetization system. This study argues that digital “dakwah” serves as a site of negotiation among spiritual values, digital capitalism, and popular culture, in which religion functions not merely as a moral message but also as an integral part of the contemporary digital media industry.